PEMANFAATAN LIMBAH CANGKANG KELAPA SAWIT PADA CAMPURAN BETON RINGAN - Indrayani, Indrayani; Sulianti, Ika; Wahyudi, Wahyudi; Herbi, Bahusin Aji Jaya (Jurusan Teknik Sipil Universitas Bangka Belitung, 2023)
Various kinds of additives have often been carried out in an effort to improve the quality of concrete so that it is higher by utilizing alternative materials that are easily available so that manufacture of concrete becomes economical. This research is the utilization of waste Shell from palm oil in the combination of light congrete where the palm oil shell is used as the substitute of rough agregat both for the half or the whole in the purpose to get the effect of the palm oil shell in making light congrete, rough agregat with the palm oil shell expected with the cultivation of palm oil waste can increase the press power of aggregat. The changing process of palm oil Shell is by counting the volume of rough agregat. The percentage variation of palm oil Shell toward the volume of rough agregat in the combination is as follows 25 percent of palm oil Shell, 50 percent of palm oil shell 75 percent of palm oil Shell and 100 percen of palm oil Shell. From the results of testing the compressive strength of concrete at the age of 28 days obtained an average of 23.86 Mpa. While the results of testing the compressive strength of concrete at the age of 28 days using palm shells at variations of 25%, 50%, 75%, and 100% have an average compressive strength value of 14.9 MPa, 11.6 MPa, 4.25 MPa, and 2.73 MPa.